Effect Size Analysis of the Implications Ethnoscience Approach to the Improvement of 21st Century Skills in Science Learning - Nurhasnah Nurhasnah*; Lufri Lufri; Asrizal Asrizal (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
Indonesia has a variety of cultures so it has a variety of local knowledge related to natural knowledge that can be used as a study of scientific knowledge. Local knowledge of natural knowledge is known as ethnoscience. Integration of ethnosciences into science learning can facilitate the various skills possessed by students. This study aims to analyze the effects of ethnoscience approaches in science learning. This research is a meta-analysis study. Research data were obtained by searching for national articles and international articles in 2017-2021 based on predetermined criteria, namely having data pretest and posttest. The search was carried out on google scholar with the keyword "ethnoscience", "science education", "biology education", "chemical education", "physical education", and "local culture". Next, as many as 26 articles were analyzed by measuring the size of the article effect. Based on the results of the data analysis carried out, the results show that the ethnoscience approach in science learning has a positive influence on improving students' abilities and is effectively used in the learning process of science 1.12 with a high category. Knowing the effects of the ethnoscience approach in science learning, it can be a choice of approach that realizes the purpose of learning science in schools and becomes one of the forums for preserving local culture for the next generation